Self-control during teacher training as one of the means of improving pedagogical professionalism (Pedagogy of Higher and Secondary Education, 2021)
This atricle is devoted to the problem of formation of the skills and habits of self-control of the teachers. The essence of the prychological process of self-control as the science conception is examined. The conditions of formation of the skills and hubits of self-control of the teachers are defined.
Keywords: self-control; skills and habits of self-control; proffesional knowledge